Sacral Defect Reconstruction Using Double Pedicled Gracilis Muscle Flap combined with Gluteal Fasciocutaneous Rotation Flap. Issue 5 (16th May 2022) - Triolo, Julie C.; Buchs, Nicolas C.; Tessitore, Enrico; Hannouche, Didier; Dominguez, Dennis E.; Kalbermatten, Daniel F.; Oranges, Carlo M.
Abstract : Summary: Several reconstructive approaches have been described for reconstruction after sacral chordomas, classically myocutaneous flaps. Recently, postural muscle preservation techniques are preferred whenever possible. We present the case of a 70-year-old man who underwent en-bloc resection of a sacral chordoma resulting in a large three-dimensional defect. To reconstruct the pelvic floor, an acellular dermal matrix and a double pedicled muscle gracilis flap were used to avoid herniation of the abdominal cavity organs. The overlying soft tissue defect was reconstructed with a unilateral gluteal fasciocutaneous rotation flap partially deepithelialized. No surgical complications were observed. Aesthetic and functional outcomes were both satisfying at 9-months postoperative follow-up. The ambulatory functions were not compromised. This combined flap reconstruction associated with a dermal matrix offers a reliable and effective option for sacral reconstruction while minimizing the morbidity.